2017
DOI: 10.1016/j.coastaleng.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of non-breaking wave induced scour depth at the trunk section of breakwaters using Genetic Programming and Artificial Neural Networks

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It is robust, simple and universal, and has a strong ability to solve complex nonlinear problems. Such as the prediction of non-breaking wave induced scour depth at the trunk section of breakwaters 8 . Furthermore, based on laboratory experimental data, Koç et al 24 suggested that GP has good potential in solving complex problems in the field of coastal engineering.…”
Section: Genetic Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is robust, simple and universal, and has a strong ability to solve complex nonlinear problems. Such as the prediction of non-breaking wave induced scour depth at the trunk section of breakwaters 8 . Furthermore, based on laboratory experimental data, Koç et al 24 suggested that GP has good potential in solving complex problems in the field of coastal engineering.…”
Section: Genetic Programmingmentioning
confidence: 99%
“…Furthermore, some formulas are complicated in form and do not indicate the actual physical process, and the prediction accuracy needs to be improved. Predictive methods such as artificial neural networks (ANNs) and genetic programming (GP) can effectively deal with complex multivariate nonlinear problems, and have been used to estimate hydraulic characteristics [7][8][9] . The main advantage of using GP for symbolic regression is that there is no need to specify the size and shape of the approximation function in advance, and the specific knowledge of the problem can be included in the search process through an appropriate mathematical function 10 .…”
mentioning
confidence: 99%
“…Examples of empirically‐based models are: Regression‐type models, Machine Learning Approaches (e.g. Pourzangbar et al, ), etc. and energetics‐type, which solve a sediment mass conservation equation (Exner equation) where the mass fluxes come from empirically‐based closure laws (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The present measures against the scour can be mainly divided into two sections according to their principles: enhancing the stability of the erodible bed and modifying the flow structure. The former mainly includes toe protection [11], revetments [12, 13] and mattresses [14], while the latter includes groins [15, 16] and submerged breakwaters [17, 18]. However, many of the measures consolidating the stability of sediment on river bed and banks, like the revetments and mattresses, would lead to some environmental and ecological problems.…”
Section: Introductionmentioning
confidence: 99%